Money Demand and Monetary Policy in the Perspective of Islamic Economics - Maharani, Dewi; Fattah, Abdul (Tawazuna, 2021)
This paper is about the concept of money demand and monetary policy in the perspective of Islamic economics. Money and monetary policy are two interesting things to discuss in the study of Islamic economics. This is due to the dynamics of the monetary sector which is growing rapidly when compared to the development of the real sector, both in theory and in practice. In fact, monetary instruments dominate the global economic system and are increasingly taking root. Money greatly affects the economy of a country and this is related to monetary policy.